Assessing TMV as an immunogenic particle : the expression of HIV-1 subtype C V3 loop neutralizing antibody epitopes on the surface of TMV virions - Valley-Omar, Ziyaad (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references (leaves 105-120).